Ensino e aprendizagem de língua inglesa na perspectiva da andragogia: uma experiência com alunos adultos - Marangoni, Vitor Emanuel Sguarezi (2018)
This research focused on a foreign language teaching-learning process, guided by andragogical principles, for an adult age group, from a language school in a western city of Paraná. From our teaching practice, we had some questions that were presented as drivers of our study: can the process of didactic mediation in teaching English as a second language, guided by the methodological principles of andragogy, provide effective learning? In order to find answers to this problem, we outlined, as a general objective, to analyze the effects of teaching by andragogical methods in the learning of English language (foreign language) by a group of adult students of a language school from the private network of teaching in the aforementioned context and as specific objectives, reflect on the concept and principles of andragogy as a learning theory for adult learners; understand the motivations and learning limitations of the adult student, before the submission of andragogical techniques; to reflect on the didactic material, development and results of a didactic mediation project, guided by the andragogic method in the teaching of English language with adult students. In order to meet the objective presented, we based the research on the theoretical assumptions of andragogy - an ancient science that studies adult education seeking for an effective learning for the development of skills and knowledge. It is a quantitative-qualitative research of an interpretative nature, in Applied Linguistics, guided by Andragogy. Data were generated through the use of a questionnaire, field diary records and the final evaluation of academic achievement of these students at the beginning level of proficiency in English. As a result of the didactic mediation project, we found out that the use of andragogical methods in teaching produced satisfactory effects on learning English as a foreign language by adult learners. This finding was evidenced by the excellent performance of the research participants in the following aspects: proficiency in speaking, reading, listening and speaking at the beginner level of English. Thus, the use of appropriate methodologies for adults has proved to be efficient in teaching and learning English in the context of the research. However, we believe they can be effective in other contexts.